Assessment of the Cimanggis Village Government's Performance in Managing the Tuesday Market in Cicantayan District, Sukabumi Regency (2023-2024) - Abdul Manan; Yana Fajar FY Basori; Dine Meigawati (Lafadz Jaya Publisher, 2025)
This study aims to evaluate the performance of the Cimanggis Village Government in managing the Tuesday Market in Cimanggis Village, Cicantayan Sub-district, Sukabumi Regency in 2023-2024, using Dunn's policy evaluation model which includes dimensions of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This research used a qualitative approach with a descriptive method, where data was collected through in-depth interviews with various informants involved in market management, both from elements of the village government, market managers, traders, and buyers. The results showed that the management of the Tuesday Market has provided tangible benefits to the community, especially in terms of ease of access and affordability of basic needs. However, there are still weaknesses in the aspects of policy responsiveness and accuracy, such as the non-optimal provision of formal communication channels, the lack of periodic evaluation, and the need for innovation to face digital competition. Therefore, improvements in management and market management strategies are needed in order to respond to the challenges and needs of the community in a sustainable manner.